Development (Frontend) of the Mobile-basedBeliin Yuks Application using the Flutter Framewor - Yopi Nugraha; Neni Nadiroti Muslihah; Yulia Shantika Sary; Sukrina Herman (Institut Pendidikan Indonesia, 2022)
Field Work Practice is a means to actualize oneself on skills or abilities, both soft skills and hard skills that have been obtained during lectures and are applied in a company or agency for several months. In this Field Work Practice report, several activities are presented during the Field Work Practice, problems or obstacles and suggestions and suggestions to improve performance and progress at CV Sumringah Metik Solusi for 3 months, starting from September 27, 202 to December 31, 2021. Placement of Practice Field Work at Cv Sumringah Metik Solusi located on Jl. Tasik-Bandung Km 52, Sasak Besi Perum Puri Kulsum Blok R No. 10 Blubur Limbangan, Garut, 44186. While carrying out the Field Work Practice, they are placed in the Programming section, while the activities or tasks carried out during street vendors include making a frontend for a mobile application needed by consumers and making a backend for the application